Co-operative Production in France and England - Cummings, Edward (Quarterly Journal of Economics, 1890)
Co-Operative Production in France and England Edward Cummings Edward Cummings Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 4, Issue 4, July 1890, Pages 357–386, https://doi.org/10.2307/1881742 Published: 01 July 1890